Corporate governance in Japan : historical roots from the Yamato to the Tokugawa eras - Jerzemowska, Magdalena (New York, NY : Routledge, 2025)
"The roots of corporate governance are rarely looked for in the ancient history of countries. Literature pays not enough attention to the impact of the country's history on the relations between economic actors and owners, known today as corporate governance. Many countries are guided by centuries-old traditions and customs, which is especially true of Japan. Japan is of particular interest because history of its corporate governance is not widely known and because it has developed a unique corporate governance model. This book aims to diagnose and trace the causes and symptoms of this uniqueness, emphasizing that it is a lasting legacy of previous eras. It examines key political, social, cultural, and economic events in Japan from its down till the 17th century in a comprehensive way and in the cause and effect aspect, combining the history, economic history and the history of corporate governance. It refers to little-known issues considered in the context of a very interesting and successful country and economy, which may arouse the desire to expand knowledge and learn about the roots of these successes. The innovative nature of the research goal and the simplicity of presentation are the advantages of this book"--
Keywords: Corporate governance -- Japan -- History; Japan -- History -- 1185-1868.; BUSINESS & ECONOMICS / Government & Business; BUSINESS & ECONOMICS / Corporate & Business History